2019
DOI: 10.1158/1541-7786.mcr-19-0068
|View full text |Cite
|
Sign up to set email alerts
|

CD71+ Population Enriched by HPV-E6 Protein Promotes Cancer Aggressiveness and Radioresistance in Cervical Cancer Cells

Abstract: A subpopulation of cells within tumors has been suggested to possess the ability to initiate tumorigenesis and contribute to resistance to cancer therapy. Identification and isolation of this subpopulation in cancer cells can be achieved by detecting specific cell-surface markers. In this study, flow cytometry analysis revealed an abundant CD71 þ subpopulation in human papillomavirus (HPV)-positive cervical cancer cells, while limited CD71 þ cells were detected in HPV-negative cervical cancer cells. Furthermor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
(51 reference statements)
1
7
0
2
Order By: Relevance
“…HPV16 E6 and E7 reduced G0/G1 cell cycle arrest, promoted a cancer stem-like phenotype and an anti-apoptotic effect, enhanced migration, invasion, spherogenesis, and increased chemoresistance and radioresistance after ionizing radiation in esophageal squamous cell carcinoma ( 210 ). A subpopulation of HPV-E6 positive cervical cancer cells enriched with CD71, a glycoprotein detected with poorly differentiated acute myeloid leukemia ( 216 ) and radioresistant glioma cells with cancer stem-like cells properties ( 217 ), demonstrated resistance to irradiation, an enhanced self-renewal ability, proliferation and tumorigenicity ( 211 ), in addition to higher transcriptional levels of some genes related to stemness including OCT-4, Nanog, ABCG2, and Bmi-1 ( 212 ). Furthermore, HPV16 E6 was shown to be actively involved in migration and invasion potentials, with elevated levels of functional and molecular markers of epithelial-to-mesenchymal transition (EMT) such as Snail, Slug, Twist, and vimentin, which could promote chemoresistance in cervical cancer ( 213 ).…”
Section: Introductionmentioning
confidence: 99%
“…HPV16 E6 and E7 reduced G0/G1 cell cycle arrest, promoted a cancer stem-like phenotype and an anti-apoptotic effect, enhanced migration, invasion, spherogenesis, and increased chemoresistance and radioresistance after ionizing radiation in esophageal squamous cell carcinoma ( 210 ). A subpopulation of HPV-E6 positive cervical cancer cells enriched with CD71, a glycoprotein detected with poorly differentiated acute myeloid leukemia ( 216 ) and radioresistant glioma cells with cancer stem-like cells properties ( 217 ), demonstrated resistance to irradiation, an enhanced self-renewal ability, proliferation and tumorigenicity ( 211 ), in addition to higher transcriptional levels of some genes related to stemness including OCT-4, Nanog, ABCG2, and Bmi-1 ( 212 ). Furthermore, HPV16 E6 was shown to be actively involved in migration and invasion potentials, with elevated levels of functional and molecular markers of epithelial-to-mesenchymal transition (EMT) such as Snail, Slug, Twist, and vimentin, which could promote chemoresistance in cervical cancer ( 213 ).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of cell surface markers in cancer can establish differentiation to target specific sites. Some research confirmed a novel affiliation between HPV-E6 oncoprotein expression and the increase in the CD55 and CD71 floor markers in most cervical cancer cells ( 60 , 61 ). The HPV-E6 oncoprotein enriched the CD55 and CD71 populations, which increased cell proliferation, cell self-renewal ability, cell migration, radioresistance, and tumorigenicity.…”
Section: Application Of Crispr-cas9 In Hpv Cancer Therapymentioning
confidence: 83%
“…The pathogenic mechanism of HPV is mainly through the viral oncoproteins E6 and E7, where E6 protein binds to the host pro‐apoptotic tumor suppressor, p53, and E7 binds to the retinoblastoma tumor suppressor protein, retinoblastoma protein (pRb), eventually causing cell proliferation, deformation, and canceration . As CRISPR‐Cas9 can efficiently cut and knock out pathogenic genes, it brings new hope for cervical cancer treatment, and it has in recent years made great progress in cervical cancer treatment (summarized in Table ).…”
Section: Cervical Cancer and Crispr‐cas9mentioning
confidence: 99%